Fortification of Fractured Instrument Removal Simulated Roots Using Several Calcium Silicate-Based Materials - Tuğrul Aslan; Yakup Üstün; Firdevs Çınar; Salih Düzgün; İbrahim Şener (Cumhuriyet University, 2018)
Objectives: The aim of this study was to evaluate the forces required to fracture roots obturated with different calcium silicate - based materials, after applying a fractured instrument removal simulation. Material and Methods: Seventy-five mandibular premolars were selected and decoronated. Then, all root canals were instrumented using Reciproc system. To mimic the root canal anatomy after the removal of a fractured instrument, each canal was enlarged with a size-3 Peeso reamer. The specimens were distributed into experimental groups according to the materials used for the root fortification: G1: Negative control, G2: ProRoot MTA, G3: Ortho MTA, G4: Biodentine, G5: Endocem MTA. Then, the teeth were embedded into acrylic blocks. A vertical fracture test was applied, and the fracture loads were recorded. Statistical interpretations were made (α=0.05). Results: G2, G3, G4, and G5 showed greater fracture resistances than G1 (P<0.05). There was no significant difference among G2, G3, G4, and G5 (P>0.05). Conclusions: Any of the tested materials could be chosen to reinforce the root after the removal of a fractured instrument.